2012
DOI: 10.1021/je200970v
|View full text |Cite
|
Sign up to set email alerts
|

Activity Coefficients of Fission Products in Highly Salinary Solutions of Na+, K+, Mg2+, Ca2+, Cl, and SO42–: Cs+

Abstract: Binary and ternary interaction parameters of the Pitzer formalism for the thermodynamic modeling of the fission product Cs+ in concentrated salt solutions of the hexary oceanic system Na–K–Mg–Ca–Cl–SO4–H2O at 25 °C were calculated from experimental isopiestic, potentiometric, and solubility data available in the literature. The obtained parameters were checked by comparing measured and predicted water activities and solubilities for binary, ternary, and quaternary systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 43 publications
4
18
0
Order By: Relevance
“…The solubility of CsCl in brines at standard temperature and pressure is approximately 11.3 mol/kg (Hu et al 2007;Scharge et al 2012). The solubility decreases with pressure and increases with temperature such that at 50 MPa and 40C its solubility in water is 11.8 mol/kg (Matsuo et al 2001).…”
Section: Waste Formsmentioning
confidence: 99%
See 1 more Smart Citation
“…The solubility of CsCl in brines at standard temperature and pressure is approximately 11.3 mol/kg (Hu et al 2007;Scharge et al 2012). The solubility decreases with pressure and increases with temperature such that at 50 MPa and 40C its solubility in water is 11.8 mol/kg (Matsuo et al 2001).…”
Section: Waste Formsmentioning
confidence: 99%
“…The solubility decreases with pressure and increases with temperature such that at 50 MPa and 40C its solubility in water is 11.8 mol/kg (Matsuo et al 2001). If SO4 is present in deep borehole fluids, Cs2SO4 may impose a limit of approximately 10 mol/kg on dissolved Cs concentration (Scharge et al 2012).…”
Section: Waste Formsmentioning
confidence: 99%
“…The parameters of Balarew et al 9 were obtained by fitting the solubility data reported by D'Ans and Busch 7 and disregarding the solubility data of Vaisfeld et al 8 Similarly, Scharge et al 10 obtained the ternary parameters by fitting the solubility data that Balarew et al have chosen, together with the isopiestic data digitalized from the graph form reported by Skripin et al 6 We calculated the equal water activity lines of the ternary system at 298.15 K with the corresponding binary and mixture parameters reported by Balarew et al 9 and Scharge et al 10 respectively. The calculated results with parameters of Balarew et al 9 or Scharge et al 10 (setting α 1 = 2, α 2 = 12), deviated from the experimental values, as shown in Figure 3a. The calculated equal water activity lines with the parameters of Scharge et al 10 (setting α 1 = −1, α 2 = 12) are roughly consistent with the experiment results, as shown in Figure 3b.…”
Section: Modelingmentioning
confidence: 71%
“…The mixture model parameters of CsCl−MgCl 2 −H 2 O ternary system have been reported by Balarew et al 9 and Scharge et al, 10 as shown in Table 6. The parameters of Balarew et al 9 were obtained by fitting the solubility data reported by D'Ans and Busch 7 and disregarding the solubility data of Vaisfeld et al 8 Similarly, Scharge et al 10 obtained the ternary parameters by fitting the solubility data that Balarew et al have chosen, together with the isopiestic data digitalized from the graph form reported by Skripin et al 6 We calculated the equal water activity lines of the ternary system at 298.15 K with the corresponding binary and mixture parameters reported by Balarew et al 9 and Scharge et al 10 respectively. The calculated results with parameters of Balarew et al 9 or Scharge et al 10 (setting α 1 = 2, α 2 = 12), deviated from the experimental values, as shown in Figure 3a.…”
Section: Modelingmentioning
confidence: 99%
See 1 more Smart Citation